Anemia and risk for cognitive decline in chronic kidney disease. Issue 1 (December 2016) - Kurella Tamura, Manjula; Vittinghoff, Eric; Yang, Jingrong; Go, Alan; Seliger, Stephen; Kusek, John; Lash, James; Cohen, Debbie; Simon, James; Batuman, Vecihi; Ordonez, Juan; Makos, Gail; et al.
Abstract Background Anemia is common among patients with chronic kidney disease (CKD) but its health consequences are poorly defined. The aim of this study was to determine the relationship between anemia and cognitive decline in older adults with CKD. Methods We studied a subgroup of 762 adults age ≥55 years with CKD participating in the Chronic Renal Insufficiency Cohort (CRIC) study. Anemia was defined according to the World Health Organization criteria (hemoglobin <13 g/dL for men and <12 g/dL for women). Cognitive function was assessed annually with a battery of six tests. We used logistic regression to determine the association between anemia and baseline cognitive impairment on each test, defined as a cognitive score more than one standard deviation from the mean, and mixed effects models to determine the relation between anemia and change in cognitive function during follow-up after adjustment for demographic and clinical characteristics. Results Of 762 participants with mean estimated glomerular filtration rate of 42.7 ± 16.4 ml/min/1.73 m2, 349 (46 %) had anemia. Anemia was not independently associated with baseline cognitive impairment on any test after adjustment for demographic and clinical characteristics. Over a median 2.9 (IQR 2.6–3.0) years of follow-up, there was no independent association between anemia and change in cognitive function on any of the six cognitive tests. Conclusions Among older adults with CKD, anemia was not independently associated with baseline cognitive function or decline.